2023
DOI: 10.3390/plants12162925
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Role of Sorghum RPAP3 in the Function of R2TP Complex: Insights into Protein Assembly in Plants

Abstract: The chaperone R2TP has multiple subunits that assist in the proper folding, assembly, and stabilization of various protein complexes in cells and its study can offer valuable insights into the regulation and maintenance of protein assemblies in plant systems. The ‘T’ component of R2TP is Tah1 in yeast, consisting of 111 residues, while its counterpart in humans is RPAP3, with 665 residues. RPAP3 acts as a co-chaperone of Hsp90 and facilitates interactions between RUVBL proteins and other complex components, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To determine whether the interaction mechanism of RPAP3 and HSP90 is conserved in plants, we modeled the structure of the TPR domain of AtRPAP3 bound to the MEEVD peptide based on the structure of the peptide bound to human RPAP3 TPR2 (Henri et al, 2018), as we could not detect the TPR of AtRPAP3 in the cryoEM analysis because it is located in a region with high flexibility. Modeling showed that the AtRPAP3 TPR can adopt a 3D structure similar to that of human RPAP3 TPR2 (Figure 7A), as shown for the TPR domain of sorghum RPAP3 (Machado Antonio et al, 2023). Alignment of RPAP3 sequences from humans and Arabidopsis showed that the six residues of human TPR2 that contact HSP90 (Henri et al, 2018) are conserved in AtRPAP3 TPR (Supplementary Figure 4; marked with red asterisks).…”
Section: The Tpr Domain Of Atrpap3 Mediates the Interaction With Hsp90mentioning
confidence: 70%
See 3 more Smart Citations
“…To determine whether the interaction mechanism of RPAP3 and HSP90 is conserved in plants, we modeled the structure of the TPR domain of AtRPAP3 bound to the MEEVD peptide based on the structure of the peptide bound to human RPAP3 TPR2 (Henri et al, 2018), as we could not detect the TPR of AtRPAP3 in the cryoEM analysis because it is located in a region with high flexibility. Modeling showed that the AtRPAP3 TPR can adopt a 3D structure similar to that of human RPAP3 TPR2 (Figure 7A), as shown for the TPR domain of sorghum RPAP3 (Machado Antonio et al, 2023). Alignment of RPAP3 sequences from humans and Arabidopsis showed that the six residues of human TPR2 that contact HSP90 (Henri et al, 2018) are conserved in AtRPAP3 TPR (Supplementary Figure 4; marked with red asterisks).…”
Section: The Tpr Domain Of Atrpap3 Mediates the Interaction With Hsp90mentioning
confidence: 70%
“…One of the functions of RPAP3 within the R2TP complex in animals and yeast is the recruitment of the chaperone HSP90 via the interaction between the conserved Cterminal end of the chaperone and the TPR domain of RPAP3 (Pal et al, 2014). The TPR domain of AtRPAP3 shows significant homology with human RPAP3 TPR2 that specifically interacts with HSP90 (Supplemental Figure 4), as observed for sorghum SbRPAP3 (Machado Antonio et al, 2023). We found that AtRPAP3 was able to interact with AtHSP90.3, one of the four highly homologous cytosolic HSP90 isoforms in Arabidopsis (Krishna and Gloor, 2001), by Y2H (Figure 2 and Supplemental Figure 3), suggesting that the role of RPAP3 in the recruitment of HSP90 is conserved in plants.…”
Section: Mapping Direct Protein-protein Interactions Of R2t With Hsp9...mentioning
confidence: 83%
See 2 more Smart Citations
“…This phenomenon emphasized the importance of HDAC inhibitors in the culture process of calluses. Antonio et al [ 8 ] cloned a putative gene corresponding to RPAP3, which plays the same role as the chaperone R2TP, in the monocot Sorghum bicolor , characterizing the SbRPAP3 protein with 396 residues. As a result, SbRPAP3 not only maintained its functions, including binding to RUVBL, Hsp90, and Hsp70, but also showed that RPAP3 performs an important function in the R2TP complex.…”
mentioning
confidence: 99%